Atypical Porcine Pestivirus as a Novel Type of Pestivirus in Pigs in China - Yuan, Jin; Han, Zhiyong; Li, Jun; Huang, Yunzhen; Yang, Jiongfeng; Ding, Hongxing; Zhang, Jingyuan; Zhu, Mengjiao; Zhang, Yangyi; Liao, Jiedan; Zhao, Mingqiu; Chen, Jinding (Frontiers in Microbiology, 2017)
Pestiviruses are highly variable RNA viruses. A growing number of novel pestiviruses has been discovered in domestic and wild species in the last two decades. Recently, a novel atypical porcine pestivirus (APPV) linked with the development of congenital tremor (CT) in neonatal pigs was described in Europe and the Americas. Here, the first Asian APPV complete polyprotein coding sequence was assembled from serum samples from newborn piglets aﬀected with CT in Southern China, and termed APPV_GD. 14 organ samples from aﬀected piglets were analyzed by quantitative RT-PCR (qRT-PCR) to investigate the tissue tropism of APPV, and 135 serum samples from pigs from 10 farms were used for identifying APPV in adult pigs. The highest genome loads were found in submaxillary lymph nodes, and PCR-based detection showed that APPV genomes were present in 7 samples from 5 farms. A phylogenetic tree was constructed based on the full-length genomes of the pestiviruses, and APPV_GD appeared on a new branch with another newly discovered atypical porcine pestivirus. Nucleotide identity analysis demonstrated that APPV_GD shared the highest nucleotide sequence identity with a German APPV. Bayesian inference was performed using 25 partial sequences of the APPV NS5B gene (528 bp) isolated from 4 countries in recent years. The most recent common ancestor (tMRCA) of the current APPV strains emerged in Germany, and then diversified and spread to Asia, the Americas and other countries in Europe. However, the result of bayesian inference could change when more APPV strains are isolated in the future. The present study is the first to report APPV in China and infers the origin and dissemination of the current strains of the virus.